BENTUK DAN KEDUDUKAN LAFADZ “KAM” DALAM AYAT-AYAT AL-QURAN - Muhammad Sayyidul Arwan; Faizah Ukhrawiyah (STIQ Amuntai, 2020)
The languages have a different language formation, because of them make many studies of linguistics, one of them is study of syntax. Study of syintax in Arabic uses Nahwu’s knowledge. The method of this research is qualitative descriptive. This research aims to know the form and position of lafadz “Kam” in the verses of the Qur’an. This researh is necessary, when someone is wrong to determine form and position of lafadz, will make error in interpretation and understanding of the text. The result of this research, the form of “lafadz Kam ’ in the Qur’an has three forms; the first “Kam Istifhamiyyah” there are six verses, the second “Kam Khobariyyah” there are fifteen verses, and the third have two forms, the form of “Kam Istifhamiyyah” and “Kam Khobariyyah”, there are two verses in Qur’an. The lafadz position kam in verses of Qur’an has three positions, namely Mubtada’ there are three verses, Maf’ul bih there are fifteen verses, and Dhorof substitute there are three verses. Keywords: Kam Istifhamiyah, Kam Khabariyyah, Al-Qur’an, Nahwu